2018
DOI: 10.3389/fpls.2018.01812
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling of Arabidopsis Roots Treated With Humic Substances: Insights Into the Metabolic and Interactome Networks

Abstract: Background and Aim: Humic substances (HSs) influence the chemical and physical properties of the soil, and are also known to affect plant physiology and nutrient uptake. This study aimed to elucidate plant metabolic pathways and physiological processes influenced by HS activity.Methods: Arabidopsis roots were treated with HS for 8 h. Quantitative mass spectrometry-based proteomics analysis of root proteins was performed using the iTRAQ (Isobaric Tag for Relative and Absolute Quantification) technique. Out of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 112 publications
5
44
0
Order By: Relevance
“…Regarding primary metabolism, HS application triggers alteration of plant gene expression and the content of chemical compounds [70] which are involved in different processes of plant physiology (e.g., Krebs cycle, metabolisms and photosynthesis) [71]. While it is generally agreed that HS increases photosynthetic pigment content [72,73], there is less consensus whether this translates into an increased rate of photosynthesis [74].…”
Section: Hs Modulation Of Primary Plant Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding primary metabolism, HS application triggers alteration of plant gene expression and the content of chemical compounds [70] which are involved in different processes of plant physiology (e.g., Krebs cycle, metabolisms and photosynthesis) [71]. While it is generally agreed that HS increases photosynthetic pigment content [72,73], there is less consensus whether this translates into an increased rate of photosynthesis [74].…”
Section: Hs Modulation Of Primary Plant Metabolismmentioning
confidence: 99%
“…Down-regulation of plasma membrane proteins was further observed in additional proteome studies involving different seedlings. For example, Roomi et al [70] reported up-regulation of enzymes in the glycolytic pathway, as well as regulation of ribosomal protein which indicated a stimulating effect of HS on energetic metabolism. They also observed down-regulation of 30 cytoplasmic enzymes, the transcription of which are regulated by several hormones (e.g., AUXs, CKs, and ABA).…”
Section: Hs Modulation Of Primary Plant Metabolismmentioning
confidence: 99%
“…Recently, the isobaric tag for relative and absolute quantification (iTRAQ) proteolytic technique was used to analyze the effects of radicular applications of HS to Arabidopsis plants during 8 h. In total, the application of HS led to the identification of 902 families of proteins involved in plant activity, and 92 families of proteins were differentially expressed in plants treated with HS. The biological function of the proteins expressed in response to the application of HS was related to the stress response, and these proteins were located mainly in the cytosol (Roomi et al, 2018).…”
Section: Effects Of Humic Substances On the Regulation Of Plant Growtmentioning
confidence: 99%
“…Humic substances (HS) comprise a major part of soil organic matter and influence soil processes and fluxes including soil fertility, water retention and the fate of xenobiotics [1]. HS can be used directly on plants in low concentrations to enhance plant growth, yield and nutrient uptake, thus constituting a category of plant biostimulants [2]. The effects of HS on plant growth and crop yield have been studied previously [3].…”
Section: Introductionmentioning
confidence: 99%
“…HS enhanced the efficiency of nutrient use, thus aiding in the assimilation of both macro-and microelements and inducing primary and secondary plant metabolism [3]. It was reported that humic acids (HA) can stimulate plant growth through the release of bioactive molecules with hormonal-like activity [4], thus directly affecting enzymatic activities of several metabolic pathways [2,5,6]. The effect of HS on plant nutrition may be mediated by the synthesis and functionality of membrane proteins, especially proton pumps that increase the electrochemical proton gradient across the plasma membrane (P) [7,8].…”
Section: Introductionmentioning
confidence: 99%